In situ nano-fibrillation of microinjection molded poly(lactic acid)/poly(ε-caprolactone) blends and comparison with conventional injection molding. Issue 113 (30th October 2015) - Ding, Weiwei; Chen, Yinghong; Liu, Zhuo; Yang, Sen
Abstract : During microinjection molding, there are highly oriented PCL nanofibrils in situ formed, while during conventional injection molding, there are oriented microfibrils in situ formed. Abstract : In this paper, the microinjection molding (μIM) of poly(lactic acid) (PLA)/poly(ε-caprolactone) (PCL) blend as well as a full comparison with the conventional injection molding (CIM) was carried out. The prepared PLA/PCL blend micropart and macropart were characterized by using various measurements. The results showed that μIM and CIM have a significantly different influence on the structure and performance of the PLA/PCL blend. μIM leads to a remarkable reduction in the domain size of PCL dispersed phase to the nanometer range, improvement in interfacial compatibility and narrower domain size distribution. Very interestingly, there are PCL nano fibrils in situ formed and oriented along the melt flow direction in the μIM micropart, i.e. the occurrence of an in situ PCL nano-fibrillation phenomenon. Comparatively, only PCL micro fibrils are formed in the CIM macropart, i.e. the occurrence of PCL micro-fibrillation. For both micropart and macropart, the shear layer shows much higher degrees of PCL nano/micro-fibrillation and orientation than the core layer. Compared with the macropart, the micropart exhibits increased PCL crystallinity and remarkably enhanced PLA crystallization capability. μIM also leads to a higher PLA degradation degree than CIM. In addition, the PLA/PCL blend micropart shows much higher mechanical performance and much more obvious double yielding phenomenon than the macropart.